Effect of ACTN3 gene on strength and endurance in soccer players - Pimenta, E. M.; Coelho, D. B.; Veneroso, C. E.; Barros Coelho, E. J.; Cruz, I. R.; Morandi, R. F.; de A. Pussieldi, G.; Carvalho, M. R. S.; Garcia, E. S.; de Paz Fernández, J. A. (The Journal of Strength and Conditioning Research, 2013)
Sports efficiency in activities in which strength and speed are the determining factors has been associated to the ACTN3 gene, which is responsible for the expression of alpha-actinin-3. Soccer is a mainly aerobic sport because of its long duration, but the acute actions that define the game demand a lot of strength and speed. The purpose of the present study was to compare the performance capacity of soccer players with different genotype groups of ACTN3 (XX, RX, and RR) in strength, speed, and endurance tests. Two hundred professional players of Brazilian soccer first division teams participated in this study. Speed, jump, and endurance test results were compared with the polymorphisms of the ACTN3 gene. It was noticed that RR individuals spent less time to run a 10-m path, compared with XX individuals (p < 0.05). The RR individuals also presented lower time rates at the 20- and 30-m path, compared with RX and XX individuals (p < 0.05). In jump tests, RR individuals presented higher rates, compared with RX and XX individuals (p < 0.05). As for aerobic tests, the XX individuals presented higher rates of VO2 max, compared with the RR group (p < 0.05), and did not differ from the RX group. The main conclusion of this study is that soccer players of genotype ACTN3/RR are the fastest in short distances and present higher jump potential. ACTN3/XX individuals presented the highest aerobic capacity. These findings can be used in training load adjustment and can influence the development of tactical schemes in soccer matches.